Called Al-Qur’an Digital Perspective; Answer To Raising Hoax In Era Of Disruption - Savhira D.L., Risma; Alaika, Alaika M. Bagus Kurnia PS; Firdaus, Dhomirotul (Tribakti: Jurnal Pemikiran Keislaman, 2020)
Disruption provides a myriad of benefits to people's lives. However, on the other hand it cannot be denied that the era of disruption has brought quite dangerous obstacles. Due to the lack of a person's moral standing in responding to the era of disruption, resulting in various problems arise. One of the big problems born in the era of disruption is the phenomenon of hoaxes. Hoax is triggered by a lack of attention to ethics in communicating with high social media user numbers. The use of this research writing method takes the form of a conceptual framework and is qualitative in nature. Some literature and observations taken from several media issues related to hoax news as data retrieval, and using a phenomenological analysis approach. This paper produces a digital piety concept that can be implemented through tabayyun attitude Qs review. al-H{ujura>t verses 6-8, politeness in language review Qs. T{aha> verse 44, and local wisdom in the language review Qs. al-Hujurat verse 12 obtained from the study of the contents of the Qur'an.